(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
The process of capital investment appraisal takes hold the attention of managers and accountants of the industrial companies. This process involves the use of multiple and diverse financial evaluation methods to measure the economic attractiveness of capital investment peojects. This multiplicity and diversity of financial evaluation metods have been the motive of this research to: investigate some organizational variables such as the desired objectives, identify managerial procedures which regulate the capital investment process, specify evaluation methods and examine the relationships between these variables and evaluation methods actually used by a sample of public industrial companies in Jordan. The data was collected by means of questionaire handed to a sample from the above-mentioned companies. In addition, the reason for selecting these companies was that the capital investment appraisal practices of the jordanian companies in the industrial sector have received little attention in previous research. The results overall indicate that there are multiple and diverse evaluation methods used in the capital investment appraisal process in the companies which participated in this research. Also, there is no single best method used for evaluating capital investment. But, the participating companies have not relied on the financial evaluation methods alone, but also used non-financial criteria. Finally, these results clearly show that there are some statistically significant relationships between the use of some financial evaluation methods and some variables under investigation. Consequently, these results imply that the use of some financial evaluation methods to measuring the economic attractiveness of capital investment peojects are related to some organizational variables which regulate the capital investment appraisal process. In conclusion, the results failed to reject the null hypotheses (1) to (5) completelly.